The Role of Civil Society Actors in Peacemaking: The Case of Guatemala (2017)
This article builds upon recent scholarship in critical peace studies that focuses on the role of civil society actors in formal peacemaking processes, in short, peace talks, and post-conflict peacebuilding. The article specifically explores the role of civil society actors in the Guatemalan peace process. The research addresses the possible tensions and potential complementarities in processes where civil society enjoys a mandated role in centralised, formal peace negotiations carried out between the state and armed actors in talks levied within the liberal peace framework. In the case of Guatemala, non-state actors participated to an unprecedented extent in the peace negotiations, and Guatemala has not relapsed into armed conflict. However, post-conflict Guatemala is a violent and unstable country. Consequently, the study challenges the assumption that peacemaking is necessarily more successful in those instances where provisions have been established to guarantee the participation of civil society. © 2017 Journal of Peacebuilding and Development.